Digoxin. (March 2016) - Dawson, Andrew H.; Buckley, Nick A.
Abstract: Digoxin and other cardiac glycosides cause a large number of cardiac effects in overdose leading to both bradyarrhythmias and tachyarrhythmias. The specific antidote, digoxin-specific antibody fragments, is expensive but effective and is generally reserved for the treatment of severe poisonings.